Panduan Kesehatan Bagi Ibu Hamil Dan Anak Berbasis Android Mobile - Lufila Fila; Muhammad Zulfadhilah (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2020)
Background: Health as a basic need for everyone is a determining factor in the quality of Human Resources. But sometimes health is often forgotten due to various factors, and most often it is because of one's own busy schedule. During this time mothers get information about pregnancy and children from Integrated Healthcare Center or at the Public health center and from midwives or doctors in their immediate surroundings. The weakness of the health service facility is the time of its implementation which cannot be done at any time. While the obstacle to get information from midwives, doctors and health centers in their immediate surroundings is the busyness of the person and the distance that is sometimes difficult to get the information.Purpose: To fulfill the health information system for pregnant women and children faster, there are now many mobile applications that are able to meet the health information needs of pregnant women and childrenMethod: Observation method and literature review.Results: The results of this study are the creation of an application, this Android-based mother and child application that is useful for obtaining information for pregnant women and children based on the parameters needed for each menuConclusion: The conclusion of this research is an Android-based information system created to help monitor health for pregnant women and children in the womb.Â Keywords: Android, Experts, Health, Pregnancy